Texas People, Texas Places : More Musings of the Rambling Boy - Taylor, Lonn, 1940-2019 (Book collections on Project MUSE., 2014)
Following up Texas, My Texas: Musings of the Rambling Boy with a second collection of essays, Lonn Taylor's Texas People, Texas Places again explores the very best of Texas geography, Texas history, and Texas personalities. In a state so famous for its pride, Taylor manages to write an exceptionally honest, witty, and wise book about Texas past and Texas present. Texas People, Texas Places is a story of men and women and places that have made this state great. From a small-town radio host to tight-fisted West Texas ranchers, and even to Taylor's own family members, Taylor's subjects paint a profound and dynamic picture. Lonn Taylor shares anecdotes that will appeal to any Texan, in a voice that is as personal as it is unique.